2014
DOI: 10.3310/pgfar02040
|View full text |Cite
|
Sign up to set email alerts
|

National trends and local delivery in old age mental health services: towards an evidence base. A mixed-methodology study of the balance of care approach, community mental health teams and specialist mental health outreach to care homes

Abstract: BackgroundThe rising number of older people with mental health problems makes the effective use of mental health resources imperative. Little is known about the clinical effectiveness and/or cost-effectiveness of different service models.AimsThe programme aimed to (1) refine and apply an existing planning tool [‘balance of care’ (BoC)] to this client group; (2) identify whether, how and at what cost the mix of institutional and community services could be improved; (3) enable decision-makers to apply the BoC f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 223 publications
(521 reference statements)
0
42
0
Order By: Relevance
“…3,4 Not only is this what people want, but enabling older people to remain at home for longer reduces the potential cost of care for government. [7][8][9] A large UK BoC study found that up to half of new care home entrants could be cared for in alternative settings. 2 The "Balance of Care" (BoC) approach, a systematic framework for exploring the potential costs and consequences of changing the mix of community and long-stay residential services in a defined geographical area 6 can be used to identify the types of dependent older people who could equally be cared for at home or in residential care.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 Not only is this what people want, but enabling older people to remain at home for longer reduces the potential cost of care for government. [7][8][9] A large UK BoC study found that up to half of new care home entrants could be cared for in alternative settings. 2 The "Balance of Care" (BoC) approach, a systematic framework for exploring the potential costs and consequences of changing the mix of community and long-stay residential services in a defined geographical area 6 can be used to identify the types of dependent older people who could equally be cared for at home or in residential care.…”
mentioning
confidence: 99%
“…5 However, shifting the focus from LTC requires better information on older people in receipt of home care, which is in line with the World Health Organization (WHO)'s recommendation for improved measurement, monitoring, and understanding of health and ageing, including in relation to older people in need of LTC. 9 For each of these case-types, nursing home care could be delayed by 3 to 12 months with sufficient community supports. [7][8][9] A large UK BoC study found that up to half of new care home entrants could be cared for in alternative settings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The local authority was interested in exploring the use of ECH as an alternative to care home placement and had recently upgraded several sheltered housing complexes into ECH for older people; however none of these were specifically dedicated to the care of people with dementia. The data were collected as part of a Balance of Care (BoC) study, which sought to identify the most appropriate mix of community and institutional services to provide for older people with mental health problems in North-West England (Challis et al, 2014;Tucker, Brand, Wilberforce, Abenstern, & Challis, 2015). Balance of care is a longstanding strategic planning framework, identifying people whose needs can be met in more than one setting (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately two-thirds had at least medium ADL dependency; more than four-fifths had medium or high levels of cognitive impairment; and a still higher proportion presented with medium or high levels of challenging behaviour. Full details of the study sample are available elsewhere (Challis et al, 2014).…”
Section: Strand 1 Care Planning Workhop Identification Of Care Hommentioning
confidence: 99%